Hank the Cowdog : The Incredible Ice Event - Book 78 - Erickson, John R., 1943- (Perryton, TX : Maverick Books, Inc., 2022)
"Woodrow, Slim's future father-in-law, is a man of few words. So, when he takes the trouble to warn Slim about an Arctic cold front that is about to descend on the Texas Panhandle, Hank knows the ranch is in for a rough time. In that kind of cold, everything quits working: pipes freeze, diesel pickups don't start, power lines break, cattle suffer, and stock tanks freeze over. And, while the dogs in town might be able to spend that kind of week camped out in front of a warm fire, the Head of Ranch Security has to be sure that the cattle have access to food and water! Will Slim and Loper be able to keep the ice at bay, or will the stock tanks freeze solid and drive the herd mad with thirst? There's only one way to find out!"--back cover.
Keywords: Dogs -- Juvenile fiction; Ranch life -- Juvenile fiction. -- West (U.S.); Ice storms -- Juvenile fiction; Western stories; Dogs -- Fiction; Ranch life -- Fiction. -- West (U.S.); Ice storms -- Fiction; Humorous fiction